2015
DOI: 10.1001/jama.2015.3860
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Dose Combination Therapy With Daclatasvir, Asunaprevir, and Beclabuvir for Noncirrhotic Patients With HCV Genotype 1 Infection

Abstract: The antiviral activity of all-oral, ribavirin-free, direct-acting antiviral regimens requires evaluation in patients with chronic hepatitis C virus (HCV) infection. OBJECTIVE To determine the rates of sustained virologic response (SVR) in patients receiving the 3-drug combination of daclatasvir (a pan-genotypic NS5A inhibitor), asunaprevir (an NS3 protease inhibitor), and beclabuvir (a nonnucleoside NS5B inhibitor). DESIGN, SETTING, AND PARTICIPANTS This was an open-label, single-group, uncontrolled internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 19 publications
9
68
0
Order By: Relevance
“…A proof-of-concept clinical trial of triple-DAA treatment (10) also showed that SOF&DCV&SMV can achieve a high SVR rate, while reducing the treatment period from 12 wk to only 3 wk using a response-guided protocol. Our analysis clearly supports a clinical advantage for triple-DAA-based IFN-free treatments as discussed elsewhere (8,10,(20)(21)(22).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…A proof-of-concept clinical trial of triple-DAA treatment (10) also showed that SOF&DCV&SMV can achieve a high SVR rate, while reducing the treatment period from 12 wk to only 3 wk using a response-guided protocol. Our analysis clearly supports a clinical advantage for triple-DAA-based IFN-free treatments as discussed elsewhere (8,10,(20)(21)(22).…”
Section: Resultssupporting
confidence: 84%
“…Triple-DAA IFNfree combinations are being clinically evaluated to seek more rapid and efficacious elimination of HCV, including NI&N-S5AI&PI and NI&NS5AI&NNI (8,(20)(21)(22). However, it is not yet understood how much advantage triple-DAA treatment can provide over double-DAA treatment, and which triple-DAA combination will give the best treatment outcome (8,(20)(21)(22). Here, we quantified the anti-HCV activity of eight candidate combinations of triple-DAA treatment; SOF with NS5AI (DCV, LDV) plus PI (SMV, ASV) or NNI (VX, DAS) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in patients with baseline NS5A RAVs treated with the NS5A inhibitor daclatasvir combined with asunaprevir (a NS3 protease inhibitor) and beclabuvir (a nonnucleoside NS5B polymerase inhibitor), SVR 12 was achieved in 25 (74%) of the 34 patients with genotype 1a infection versus all 17 (100%) patients with genotype 1b infection (23). There was no evident association between baseline NS3 or NS5B variants and SVR 12 .…”
Section: Discussionmentioning
confidence: 99%
“…peginterferon/ribavirin, suggesting that asunaprevir has no clinically meaningful effect on beclabuvir [39]. Daclatasvir, asunaprevir and beclabuvir are currently in phase 3 development as a fixed-dose combination [40,41].…”
Section: Pharmacokinetics Of Asunaprevir In Combination With Daclatasmentioning
confidence: 99%